Kaji Eksperimental Pengaruh Fase Operasi Unit Tungku Garam Semi Modern Terhadap Prestasinya - Mirza Mirza; Khairil Khairil; M. Ilham Maulana (Jurnal Teknik Mesin Unsyiah, 2016)
Heating furnace which has been used by farmers to boil salt feed water is a traditional wood-fired furnance that is very simple and very inefficient. Researchers have made several modifications to the furnace unit multi-pot configuration that can utilize waste heat in order to improve the efficiency of the furnace. Potential waste heat of exhaust gas can be used as preheater. The methodology used to asses the performance on the furnace in water boiling test method operating condition of the cold start, hot start, and simmer. The data obtained then analyzed, the result showed that the burning rate and fire power that occurred during the cooking procces of the operation conditions of the cold start, hot start, and simmer increase, but the thermal efficiency decrease. This indicates that increasing of combustion efficiency has not been able to be utilized to the maximum heat. Value of the thermal efficiency of the furnace is affected by the value of useful energy to heat the water in the pot and the amount of energy entry/energy of combustion.